1990
DOI: 10.1101/gad.4.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Serum and v-src increase the level of a CCAAT-binding factor required for transcription from a retroviral long terminal repeat.

Abstract: Transcription from the long terminal repeat (LTR) of Rous sarcoma virus (RSV) in rat 3Y1 fibroblasts was dependent on the presence of serum. Within 1 hr after addition of serum to a serum-deprived culture, there was a fivefold increase in the level of transcripts initiated at the LTR. This stimulation did not require synthesis of new proteins. The induction of transcription by serum was mostly dependent on two CCAAT boxes in the LTR. Within 1 hr after addition of serum, there was also an increase in the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 63 publications
(57 reference statements)
0
41
0
Order By: Relevance
“…Thus, transcriptional regulation involving the v-srcresponsive unit identified in this work seems to correlate primarily not with pp6Ovsrc transforming activity but with its mitogenic capacity. Serum stimulation and the v-src product have been shown to be indistinguishable and interchangeable in activating the expression of at least some immediate-early genes (7,17,18,36,53,60). This effect is dependent on an increase in intracellular tyrosine phosphorylation (18) and is usually mediated by TPA-or serum-responsive elements (7,22,29,30,58,67,68).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, transcriptional regulation involving the v-srcresponsive unit identified in this work seems to correlate primarily not with pp6Ovsrc transforming activity but with its mitogenic capacity. Serum stimulation and the v-src product have been shown to be indistinguishable and interchangeable in activating the expression of at least some immediate-early genes (7,17,18,36,53,60). This effect is dependent on an increase in intracellular tyrosine phosphorylation (18) and is usually mediated by TPA-or serum-responsive elements (7,22,29,30,58,67,68).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the negative regulation of QR1 gene transcription by the v-src protein correlates primarily with the capacity of pp6ovsrc to induce proliferation of NR cells and not with its ability to transform these cells (27,28 (7,8,15,53,58). However, other sites such as PEA3 (66), CCAAT (18), PRD II/KB (15), and TATAA (3) have been implicated in certain cases. In contrast, there have been only a few reports of genes whose expression is negatively regulated by the v-src gene product, including tropomyosin (31), muscle-specific genes (19), QR1 (28), and the MARCKS protein (38).…”
mentioning
confidence: 99%
“…A mechanism common to several cell types may be responsible for altering cell growth and would involve the induction of immediate-early genes by targeting ubiquitously expressed transcription factors (5,9,20,23,35,37,67,70,82). A second pathway would negatively regulate differentiationspecific genes by targeting developmentally controlled transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have investigated the mechanisms that lead to transcriptional stimulation of genes by the v-Src protein (5,9,20,23,35,37,67,70,82). In several cases, positive regulation of transcription involves TRE or CRE elements and their cognate transcription factors of the leucine zipper family.…”
mentioning
confidence: 99%
“…Because the histone-like subunits NF-YB and NF-YC have high intrinsic affinity for nucleosomal structures (41,42), NF-Y binding to the CCAAT element can preset the chromatin configuration for coactivators to be recruited (12,69). In these studies, however, the coactivators c-Jun and E1A stimulate basal promoter activity of bsp by recruiting NF-Y to the BSP ICE box in a mechanism that functions independently of p300/CBP and P/CAF HAT activity.…”
Section: Discussionmentioning
confidence: 77%